Farmers' Perception and Adoption Level of Beef Cultivation Technology (Case of Livestock Farmer Group in Bunga Mas District, South Bengkulu Regency) - Emlan - Fauzi; Marzan Marzan; Erpan Ramon; Andi Ishak (SINTA Journal (Science, Technology, and Agricultural), 2021)
The adoption of beef cattle cultivation technology will be determined by the farmer's perception of the technology. This study aims to determine the perception and level of adoption of beef cattle farming technology in Bunga Mas District, South Bengkulu Regency. The research was carried out from August to September 2021. Data collection through FGDs involved 19 participants consisting of 9 farmers from two farmer groups, 7 agricultural extension workers from BPP Bunga Mas, and 3 BPTP Bengkulu researchers. The data collected includes farmer's perception and adoption of the technology components of beef cattle cultivation, namely beef cattle mating technology with artificial insemination (AI), vaccination and administration of vitamins and medicines, provision of superior grass, giving concentrate, and utilization of livestock waste as organic fertilizer. The assessment of perception and adoption is assessed based on 4 categories. Perception and adoption are categorized as less good if they are at level 1-2, while the good category is on a scale of 3-4. Data were analyzed descriptively. The results showed that the perception of farmers in Bunga Mas District, South Bengkulu Regency on the components of beef cattle cultivation technology was included in the good category. Meanwhile, the level of farmer adoption of the technology component varies. The level of farmer adoption of the technology component of beef cattle cultivation has never been higher than the farmer's perception. Based on the conclusions obtained from the results of this study, it is suggested that it is necessary to encourage increased adoption of breeders for the application of technology, especially AI technology and the use of superior grass.